2001
DOI: 10.1111/j.1365-2338.2001.tb00977.x
|View full text |Cite
|
Sign up to set email alerts
|

Collar rot of Chlorophytum borivilianum caused by Corticium rolfsii: a new disease

Abstract: Ha M0no)JbIx MaCJIHHaX, BbIPaIUeHHbIX H3 3eJIeHblX YepeHKOB (Ha CTiSqHH Be~TWBHOTO pa3MHO)KeHWII W B OTKPbIToM rpYHW), 6~n o ki30JIWpoBaHO Y e T b l p e BWa I-PM~OB: Macrophomina phaseolina, Nectria haematococca, Armillaria mellea, Corticium roljsii. 06cnenoeaHan MeCTHOCIH W JIa60paTOpHbIe aHWlU3bI nO3BOJIWnW WX YCTaHOBUTb W BbIIIBWTb. Bibliographie Boulila M (1994) Le deptrissement de I'olivier en Tunisie: premiers risultats de recherche et perspectives d'avenir. 72rnes Journies Biologiyues Sociifi Chirnie Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The various workers recommended the introduction of N, P 2 O 5 and K 2 O in the range of 25-75, 60-65 and 2-30 kg/ha, respectively, for higher tuber yield (Anonymous, 2002, Kothari andPaturde et al 2000;Singh et al, 2004a;Wankhade et al, 2004). The studies showed that application of NPK in the ratio of 25:25:25, 50:50:50 and 45:60:60 kg/ha or farmyard manure (FYM) (10-40 t/ha) alone or in combination with NPK, greatly enhance the yield of fresh tubers (Anonymous, 2003;Anonymous, 2005b;Chauhan et al, 2005;Chouhan and Joshi, 2002;Ingle et al, 2004;Kothari and Singh, 2003;Paturde et al, 2002;Singh et al, 2001a;Wankhade et al, 2004). The availability of water in the fields also directly effects the uptake of primary (NPK), secondary (S, Mg, Ca, Fe) and micro (Cu, Zn, Mn) nutrients in C.…”
Section: Nutrient Managementmentioning
confidence: 96%
“…The various workers recommended the introduction of N, P 2 O 5 and K 2 O in the range of 25-75, 60-65 and 2-30 kg/ha, respectively, for higher tuber yield (Anonymous, 2002, Kothari andPaturde et al 2000;Singh et al, 2004a;Wankhade et al, 2004). The studies showed that application of NPK in the ratio of 25:25:25, 50:50:50 and 45:60:60 kg/ha or farmyard manure (FYM) (10-40 t/ha) alone or in combination with NPK, greatly enhance the yield of fresh tubers (Anonymous, 2003;Anonymous, 2005b;Chauhan et al, 2005;Chouhan and Joshi, 2002;Ingle et al, 2004;Kothari and Singh, 2003;Paturde et al, 2002;Singh et al, 2001a;Wankhade et al, 2004). The availability of water in the fields also directly effects the uptake of primary (NPK), secondary (S, Mg, Ca, Fe) and micro (Cu, Zn, Mn) nutrients in C.…”
Section: Nutrient Managementmentioning
confidence: 96%
“…Later, small pinhead black dots marked the spot that represent the pycnidia. Singh et al (2001) have observed infection of Corticium rolfsii Curzi. in the experimental field.…”
Section: Diseases and Pestsmentioning
confidence: 99%
“…lower leaves and small brown necrotic lesions in the collar area of the plant occurs(Singh et al, 2001;Trivedi et al, 2006).…”
mentioning
confidence: 99%